Starcie kultur prawnych: Przekład na język angielski jako język komunikacji interkulturowej - Goddard, Christopher (Investigationes Linguisticae, 2009)
Increasing supranational legislation and other factors fuel interaction between legal cultures. This leads to greater need both for a new breed of international lawyer and for legal translators. Moreover, the rise of English as the de facto global legal language intensifies the need for translation of legal texts into English and, as a corollary, production of legal texts in English. In practice, both involve individuals whose native tongue is other than English (NNS) in an endeavour fraught with traps for the unwary. To illustrate against the relevant theoretical background, legal texts are presented that involve the author as translator into English from French, German, and Russian, and as reviser, editor, and proofreader of English-language legal text prepared by NNS. Findings suggest a need to equip practitioners with certain knowledge and skills, implying a corresponding need for education, training, and legal linguistic research.